2007
DOI: 10.1111/j.1365-2567.2007.02618.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal–fetal interaction: preconception immunization in mice prevents neonatal sensitization induced by allergen exposure during pregnancy and breastfeeding

Abstract: Summary Allergen exclusion measures during pregnancy and lactation have been given consideration in studies of primary allergy prevention but complete avoidance of mother/neonatal allergen exposure has proven to be a difficult procedure. To evaluate a strategy to prevent allergen sensitization in early life in mice, we first established a neonatal model with ovalbumin sensitization through maternal allergen exposure during pregnancy or breastfeeding. The modulatory potential of preconception immunization was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 25 publications
3
50
1
8
Order By: Relevance
“…Maternal sensitization prior to pregnancy has been reported to provide a degree of protection against subsequent pup sensitization to homologous allergen (Fusaro et al, 2002(Fusaro et al, , 2007Victor et al, 2003). Gestational allergen exposure was demonstrated to confer similar protection, especially if dams had also been sensitized prior to breeding (Melkild et al, 2002;Uthoff et al, 2003;Fusaro et al, 2007). In some cases, this protection was attributed to maternal antibody "interference" with neonatal immune responses, as the effects disappeared if pup sensitization was delayed until after maternal antibodies were cleared (Uthoff et al, 2003;Victor et al, 2003).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Maternal sensitization prior to pregnancy has been reported to provide a degree of protection against subsequent pup sensitization to homologous allergen (Fusaro et al, 2002(Fusaro et al, , 2007Victor et al, 2003). Gestational allergen exposure was demonstrated to confer similar protection, especially if dams had also been sensitized prior to breeding (Melkild et al, 2002;Uthoff et al, 2003;Fusaro et al, 2007). In some cases, this protection was attributed to maternal antibody "interference" with neonatal immune responses, as the effects disappeared if pup sensitization was delayed until after maternal antibodies were cleared (Uthoff et al, 2003;Victor et al, 2003).…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies in mice investigating the effects of maternal sensitization and/or gestational exposure on subsequent pup responses to homologous allergen have produced conflicting results. Maternal sensitization prior to pregnancy has been reported to provide a degree of protection against subsequent pup sensitization to homologous allergen (Fusaro et al, 2002(Fusaro et al, , 2007Victor et al, 2003). Gestational allergen exposure was demonstrated to confer similar protection, especially if dams had also been sensitized prior to breeding (Melkild et al, 2002;Uthoff et al, 2003;Fusaro et al, 2007).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Following sensitization with D pteronyssinus, the offspring of immunized mothers had decreased specific IgE compared to control normal offspring. A more recent study from the same group (Fusaro et al, 2007) demonstrated that 'immunized' mothers exposed to antigen during pregnancy or breastfeeding underwent intense vertical transmission of antibodies, including IgG in complex with ovalbumin and IgG 1 antibody with "anaphylactic function. "…”
Section: Allergen Modelsmentioning
confidence: 99%
“…Este fato salienta que a imunização prévia das mães é um procedimento profilático para evitar a sensibilização precoce das proles (FUSARO et al, 2007).…”
Section: Desenvolvimento Da Resposta Alérgicaunclassified